A Variance Decomposition Analysis of the Information in the Term Structure - EDERINGTON, Louis H. (Institutional Knowledge at Singapore Management University, 1997)
Based on a market efficiency assumption, we use variance decomposition analysis is to separate information in the term structure on expected future spot rates from information on time-varying term premia and to examine the market's ability to forecast both future rate changes and excess returns on long versus short securities. We find that fluctuations in the slope of the yield curve are due more to changing term premia than to fluctuations in expected future spot rates and that the market correctly predicts about 40 percent of the month-to-month changes in spot rates, a considerably higher percentage than that found by previous studies.